The Question of Lag: An Exploration of the Relationship Between Conductor Gesture and Sonic Response in Instrumental Ensembles - Meals, Cory D. (Frontiers in Psychology, 2020)
Group musical performance, especially large instrumental ensembles, present the outward appearance of an asymmetric, temporally immediate stimulus-response relationship between conductor and ensemble. Interestingly, anecdotal reports from both conductors and performers indicate a degree of variability in the timing of orchestral response to the conductor’s gestures. This observation is not present in anecdotal accounts of other instrumental ensemble settings, like wind bands, but commonplace occurrence among orchestral musicians indicates the potential presence of greater complexity in the observed relationship. This study investigates both the quality and quantity of temporal lag between conductor and ensemble in two common instrumental ensemble configurations – wind bands and orchestras – in an effort to describe the interplay present within conducted group performance. The findings indicate that the anecdotally identified lag is present within all ensemble types, and that it presents a flexible, dynamic temporal relationship between conductor and ensemble. Additionally, both the quantity and quality of lag values are significantly different between ensemble types, experience levels, and musical content. Several avenues for future research are identified and confounds within the sampled ensembles are examined for their potential roles in the observed relationships.